“Cause they’re girls/boys”: preschool children’s play and toy choices - Özkan-Kunduracı, Hurşide Kübra (Frontiers in Psychology, 2025)
This case study aims to determine children’s play and toy preferences that they think are specific to girls and boys. The study group consisted of 50 children (21 girls, 29 boys) aged 48–72 months, attending a preschool in İstanbul, Türkiye. The data were obtained through pictures and semi-structured interviews and evaluated through descriptive analysis. As a result, the opinions on the plays by both girls and boys were mostly gathered under “pretend play.” Children included the physical movement type of play in a minority of the girls’ plays. In addition, children expressed their opinions mostly in the “representative toys” category. On the other hand, differences were observed in the types of representative toys in the girls’ and boys’ toys. While boys’ toys in this category were frequently cars, imaginary heroes, and army toys; girls’ toys were frequently dolls, character-figure toys, and doll houses. As another result, both girls and boys mostly reported gendered expressions and expressions of emotions regarding the motivations for the plays by children. In line with these results, both girls’ and boys’ views on plays and toys differ depending on gender but, both girls’ and boys’ views are parallel to each other.